MANAJEMEN SEKOLAH ISLAM DAN PEMBELAJARAN BERBASIS EDUTAINMENT (EDUKASI DAN ENTERTAINMENT) - Syafar, Djunawir (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Islamic schools continue to face challenges such as low student motivation and monotonous learning environments. This study aims to examine the relevance of Islamic school management and edutainment-based learning approaches in addressing these issues. Using a library research method, data were obtained from journals, books, theses, dissertations, and online articles. The findings indicate that: (1) Edutainment promotes enjoyable and engaging learning experiences that enhance student motivation; (2) Edutainment-based Islamic school management emphasizes creativity, innovation, and a humanistic approach; (3) The principles of edutainment align with Islamic educational values that focus on humanizing students. Therefore, edutainment offers a strategic approach to improving both management and learning practices in Islamic schools